Country size and the survival of authoritarian monarchies: developing a new argument. Issue 2 (17th February 2020) - Jugl, Marlene
ABSTRACT: This article combines the literature on authoritarian regime survival with that on small states to propose a new explanation for the survival and breakdown of authoritarian monarchies. To develop the conjecture that monarchy tends to survive in small countries into a theoretically and empirically sound argument, I follow the process of iterative induction. I first inspect all authoritarian monarchies between 1946 and 2018 and find that countries with monarchic survival have a significantly smaller population size than countries where monarchy broke down. Second, I develop a theoretical explanation for this relation: the feeling of vulnerability, the social proximity, and institutional centralization, which are all typically ascribed to small countries, facilitate the stability of monarchic regimes. I conceptualize this stability with Gerschewski's model of three pillars of authoritarian stability, co-optation, repression and legitimation; and I argue that smallness enhances each of these three via several channels. Third, to illustrate the plausibility of this explanation I compare two most likely historical cases of monarchies with diverging outcomes: Jordan and Egypt. Fourth, I inspect deviant cases, particularly Bhutan, Maldives and Tonga, to refine and finalize the argument. The main finding is that smallness prevented the violent breakdown of monarchic regimes since 1946.